2017
DOI: 10.1177/2047487317712601
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined exercise training and electromyostimulation treatments in chronic heart failure: A prospective multicentre study

Abstract: Background Exercise training as part of a comprehensive cardiac rehabilitation is recommended for patients with cardiac heart failure. It is a valuable method for the improvement of exercise tolerance. Some studies reported a similar improvement with quadricipital electrical myostimulation, but the effect of combined exercise training and electrical myostimulation in cardiac heart failure has not been yet evaluated in a large prospective multicentre study. Purpose The aim of this study was to determine whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…7 Following proof-of-concept studies by Coats et al 8 and Hambrecht et al 9 which documented the efficacy and safety, respectively, of exercised-based cardiac rehabilitation (ebCR), multiple studies documented its potential to improve functional capacity, QoL and prognosis in patients with heart failure. [10][11][12][13][14][15][16][17] In these studies, however, the populations under investigation were heterogeneous with respect to LV-EF (<35% up to >50%), New York Heart Association (NYHA) classification, and follow-up period. However, the effect of ebCR on morbidity and mortality on top of evidence-based state-of-the-art pharmaco-and device-therapy in high-risk patients with moderately to severely reduced LV-EF is not yet fully established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Following proof-of-concept studies by Coats et al 8 and Hambrecht et al 9 which documented the efficacy and safety, respectively, of exercised-based cardiac rehabilitation (ebCR), multiple studies documented its potential to improve functional capacity, QoL and prognosis in patients with heart failure. [10][11][12][13][14][15][16][17] In these studies, however, the populations under investigation were heterogeneous with respect to LV-EF (<35% up to >50%), New York Heart Association (NYHA) classification, and follow-up period. However, the effect of ebCR on morbidity and mortality on top of evidence-based state-of-the-art pharmaco-and device-therapy in high-risk patients with moderately to severely reduced LV-EF is not yet fully established.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of ebCR on morbidity and mortality on top of evidence-based state-of-the-art pharmaco-and device-therapy in high-risk patients with moderately to severely reduced LV-EF is not yet fully established. [10][11][12][13][14][15][16][17] Although current guidelines recommend ebCR as an effective and safe therapeutic intervention, 1,2,6 HFrEF patients are still clearly underrepresented in CR settings worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…7 The beneficial effect combining exercise training with muscle electrical stimulation has been proposed to overcome barriers in improving exercise tolerance. 8 In a large senior advanced heart failure population, self reported physical activity level conducted before heart failure decompensation was inversely related to mortality. Also, after multivariate analysis, physical activity score predicted mortality independently of several demographic and clinical variables.…”
Section: In Advanced Chronic Heart Failurementioning
confidence: 99%
“…Nevertheless, this beneficial effect of superimposed EMS is still discussed controversially since not all studies could confirm these findings . When adding EMS to voluntary contraction in patients already exhibiting muscle atrophy, like CHF, a recently published multicentre randomized prospective study in 91 CHF patients reported no additional improvement in exercise capacity and quality of life when adding EMS to an exercise training program . Additional current clinical trials are performed in different patients cohort (NCT03306056, NCT03020693), and their results will add additional information to this topic.…”
Section: Human Datamentioning
confidence: 99%